If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2/5(x-2)=-3
We simplify the equation to the form, which is simple to understand
2/5(x-2)=-3
Simplifying:
+ 0.4*(x-2)=-3
Reorder the terms in parentheses
+( + 0.4x-0.8)=-3
Remove unnecessary parentheses
+ 0.4x-0.8=-3
We move all terms containing x to the left and all other terms to the right.
+ 0.4x=-3 + 0.8
We simplify left and right side of the equation.
+ 0.4x=-2.2
We divide both sides of the equation by 0.4 to get x.
x=-5.5
| 35-3x=15x+15 | | 4x+2(x+6)=38 | | 7-9x=124-30x | | 7x-8=3-2x | | 5(z+7)= | | 118-4x=3x+20 | | -27x-3x=8-10x | | 1.1x-2.2+x-4.5= | | 6c+2c= | | 81u^4-1=0 | | -2a^2+30a=4a+60 | | x+4-2(x-1)=7 | | (k+5)x*2-10x+3=0 | | 7x+9=x+3 | | -11x-12=-12 | | 3x+1=x^2-2x+1 | | 15-3x=x-7 | | x(x-m)=12m^2 | | 3v^2-10v=8 | | -7y=x+56 | | (3ab)(2ab)= | | Z^2+3z-54=0 | | 2x^3+22x^2+60x=0 | | x^5-20x^2+20=0 | | 2x^3+22x^2+48x=0 | | 3n+7=-28 | | 5m-8m=18 | | [2x-1]3=7 | | t+32=16 | | 0.5x+7=2x-7 | | 5(2-g)=03 | | f(-4)=5x+1 |